Isolation of bothrasperin, a disintegrin with potent platelet aggregation inhibitory activity, from the venom of the snake Bothrops asper - Pinto, Adrián (2003)
The venom of Bothrops asper induces severe coagulation disturbances in accidentally envenomed humans. However, only few studies have been conducted to identify components that interact with the hemostatic system in this venom. In the present work, we fractionated B. asper venom in order to investigate the possible presence of inhibitors of platelet aggregation. Using a combination of gel filtration, anion-exchange chromatography, and reverse-phase high performance liquid chromatography, we isolated an acidic protein which shows a single chain composition, with a molecular mass of ~8 kDa, estimated by SDS-polyacrylamide gel electrophoresis. Its N-terminal sequence has high similarity to disintegrins isolated from different snake venoms, which are known to bind to cellular integrins such as the GPIIb/IIIa fibrinogen receptor on platelets. The purified protein exerted potent aggregation inhibitory activity on ADP-stimulated human platelets in vitro, with an estimated IC50 of 50 nM. This biological activity, together with the biochemical characteristics observed, demonstrate that the protein isolated from B. asper venom is a disintegrin, hereby named “bothrasperin”. This is the first disintegrin isolated from Central American viperid snake species.